In vitro evaluation on novel modified chitosan for targeted antitumor drug delivery - Qu, Ding; Lin, Haijiao; Zhang, Nan; Xue, Jingwei; Zhang, Can (Carbohydrate polymers, 2013)
► Synthesis and characterization of novel amphiphilic chitosan derivates as drug delivery system. ► Introduction of phthalyl groups could lower CMC and improve solubility in aqueous and organic system. ► Drug-loaded micelles with small particle size, narrow distribution and high drug loading efficiency. ► Enhancement on cellular uptake by active tumor targeting. ► Mechanism of cellular uptake varied from different surface properties. In this study, a novel amphiphilic copolymer designed as N-octyl-N-phthalyl-3,6-O-(2-hydroxypropyl) chitosan (OPHPC) were synthesized and then conjugated with folic acid (FA-OPHPC) to produce a targeted drug carrier for tumor-specific drug delivery. OPHPC and FA-OPHPC were characterized by FT-IR, 1H NMR, 13C NMR and elemental analysis. Paclitaxel (PTX) loaded OPHPC micelles (PTX-OPHPC) with well-defined spherical shape and homogeneous distribution exhibited drug-loading rate ranging from 33.6% to 45.3% and entrapment efficiency from 50.5% to 82.8%. In the cellular uptake studies, PTX-OPHPC brought about a significantly higher amount of PTX accumulated in human breast adenocarcinoma cell line (MCF-7 cells) compared with Taxol®. Moreover, the cellular uptake of PTX in PTX loaded FA-OPHPC micelles (PTX-FA-OPHPC) was 3.2-fold improved in comparison with that of PTX-OPHPC. The results revealed that OPHPC micelle might be a promising drug carrier for promoting PTX cellular uptake and FA-OPHPC micelle could be used as a potential tumor-targeted drug vector.